Sensory Characteristics and Protein, Iron, and Zinc Contents of Tuna Sprinkle Powder Combined with Tempeh and Moringa Leaves for Stunting Prevention - Darni, Joyeti; Wahyuningsih, Retno; Suranadi, Luh; Kurniasari, Yulinda (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2026)
Stunting remains a chronic nutritional problem and a major public health concern in Indonesia. It not only impairs physical growth but also affects cognitive development and overall child health. Adequate protein intake is one of the nutritional strategies to help prevent stunting. Sprinkle powder formulated from tuna flour, tempeh flour, and moringa leaf flour is a high-protein food product that can be conveniently added to meals, beverages, or complementary foods. This study aimed to evaluate the sensory characteristics and determine the protein, iron (Fe), and zinc (Zn) contents of the sprinkle powder. This experimental study employed a completely randomized design (CRD) with four formulations: F1 (80% tuna flour, 15% tempeh flour, and 5% moringa leaf flour), F2 (70%, 20%, and 10%), F3 (60%, 25%, and 15%), and F4 (50%, 30%, and 20%). Sensory evaluation was conducted by 25 semi-trained panelists, and the data were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney test. Significant differences were observed in color, taste, and overall acceptability among the formulations. Formula F1 was identified as the best formulation because it achieved the highest sensory scores and was the most preferred in terms of color, aroma, taste, and texture. Nutrient analysis of the selected formulation showed protein, iron (Fe), and zinc (Zn) contents of 42.7%, 10.17 ppm, and 5.18 ppm, respectively. Although the sprinkle powder demonstrated good sensory acceptability, it did not meet the requirements of SNI 01-7111.1-2005 for instant complementary foods because its protein content exceeded the maximum allowable level, whereas its iron (Fe) and zinc (Zn) contents were below the minimum required levels.